Pengembangan Desa Air Mesu Timur sebagai Sentral Produsen Bawang Merah di Pulau Bangka - Kartika Kartika; Winda Wahyuni; Yulia Yulia (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
The Bangka Belitung Islands are one of the regions with high shallot consumption. This is not comparable to the total local shallot production on Bangka Island, so it must be supplied from outside the region. Central Bangka Regency is the center of horticultural commodity production on Bangka Island. Air Mesu Timur Village has the potential to become a shallot production center on Bangka Island, but its development is hampered by limited business capital, low-quality seeds, and suboptimal implementation of standard operating procedures (SOPs) for cultivation. The Timur Makmur Farmers Group is one of the shallot producers in Air Mesu Timur Village. This activity aims to improve the implementation of SOPs for shallot cultivation and increase local farmers' yields. The program methods include Focus Group Discussions (FGDs), provision and delivery of production facilities and infrastructure, shallot cultivation demonstration plots, and shallot marketing. Community service activities will be carried out from June to September 2025 at the Timur Makmur Farmers Group's garden in Air Mesu Timur Village. The results of the activity showed increased farmer interest in growing shallots, and the demonstration plot was able to produce 500 kg of fresh bulbs from 50 kg of seeds, equivalent to a yield ratio of 1:10. The results of the agricultural business analysis showed that shallot cultivation in Air Mesu Timur Village produced a R/C ratio of 1.43. This indicates that the cultivation effort is economically profitable. Based on this activity, it was discovered that implementing the SOP for shallot cultivation typical of Bangka Island can increase shallot production and productivity on Bangka Island.